Strategy of the Village Head in Handling Covid-19 in Palae Village South Sinjai District Sinjai Regency - Sani, Kiki Rasmala; Ernawati, Ernawati; Jusmiati, Jusmiati (PINISI Discretion Review, 2022)
The Sinjai Regency Government in optimizing the handling of Covid-19 implemented a policy in five stages of handling the corona virus, namely the prevention stage, the handling stage, post-covid-19, stimulant assistance to affected SMEs and the fulfillment of social safety nets. The purpose of this study was to find out how the village head's strategy in handling covid-19 in Palae Village, South Sinjai District, Sinjai Regency. The research method used is qualitative research. Data collection techniques used are observation, interviews and documentation. The types of data used are primary and secondary data. The informants in this study were the Head of Palae Village; Village Consultative Body (BPD); Village officials; Covid Safe Village Volunteers; and Community Leaders. Data analysis techniques used are data collection, data reduction, data presentation, and drawing conclusions. The results of this study describe the Village Head's strategy in handling covid-19 through the application of PERBUP Sinjai Article 9 Number 27 of 2020. Then form a management called Covid-19 Safe Village Volunteers, conduct socialization related to handling Covid-19, and prepare village alert cars. Distribution of aid in the form of goods, namely the distribution of masks to residents, while cash assistance, namely Direct Cash Assistance (BLT).